Impact of Drug Abuse on Cases of Sleep Disorders (Insomia) and Anxiety Disorders (Anxiety) : Literature Review - Elsiana, Issabella; Salman, Salman (Sean Institute, 2022)
Drug abuse is the regular or intermittent use of external drugs for at least one month without a doctor's prescription. Drug abuse is divided into two, namely drug abuse and drug misuse, drugs are often found in cases of sleep disorders and anxiety. According to the CDC, as many as 15,000 people have lost their lives to drugs. The adverse effects of other drugs that users feel directly, namely psychological effects such as emotional changes and physical effects such as sensory dysfunction and body functions. The purpose of this study was to determine the effect of drugs on cases of insomnia and anxiety. The method used in this article review is to conduct a literature search on databases from Google Scholar, PubMed and Science Direct with a maximum year of publication in the last 10 years. The results, the results, between disorders, relationships and drug relationships were found. Drug abuse in cases of insomnia and anxiety is caused by a lack of knowledge about the proper use of drugs and the long-term side effects of using inappropriate drugs that lead to dependence. The effect on health is in the form of difficulty concentrating, reduction, decreased drug dose sensitivity, mental changes and behavior of users. The treatment needed in these cases is in the form of further handling of the dose and therapy required by the doctor, non-pharmacological therapy and avoiding triggers for the recurrence of treatment behavior. For this reason, it is necessary to monitor, prevent and properly handle drug cases to minimize the occurrence of excess drug risks.